Optimal Taxation in Search Equilibrium with Home Production - Bertil Holmlund; Ann-Sofie Kolm (Center for Economic Studies and ifo Institute (CESifo), 2001)
The paper develops a two-sector general equilibrium search model where 'goods' are produced exclusively in the market and 'services' are produced both in the market and within the households. We use the model to examine how unemployment and welfare are affected by labor taxes in general and sectoral tax differentiation in particular. We find that a tax cut on services reduces unemployment whereas a tax cut on goods has no effect. A reform involving tax differentiation, with lower taxes on services, is welfare improving. Numerical calibrations of the model suggest that the welfare gains from tax differentiation are large if the government absorbs a substantial fraction of GDP.
Keywords: 330; taxation; home production; search; unemployment